Rice Productivity Variety Ir-64 Using System Of Rice Intensification (Sri) Method With Several Models (Tegel And Legowo) - Abdul Wachid; Mintono Mintono (Universitas Muhammadiyah Sidoarjo, 2017)
The aim of this research is to know the effect of system of rice intensificstion (SRI) method with cropping and legowo planting model and the use of number of seeds per planting hole to productivity of IR-64 varieties. This research was conducted in Kedanten ham- let, Wonokoyo, Beji Sub-district, Pasuruan Regency which took place in March 2017 until June 2017. This research was conducted using Factorial Randomized Block Design (RAK) and advanced test using DMRT test at 5% confidence level. The first factor is planting model which consist of 2 level that is planting model of tegel and legowo plant- ing model, while the second factor is the use of the number of seeds per planting hole consisting of 3 levels ie 1 seed, 2 seeds and 3 seeds. Based on the observation that there is no interaction between planting model and the number of seedlings per planting hole, but in the treatment of planting model has a very significant effect on rice productivity of IR-64 variety. The best treatment is the use of legowo planting model with 2 seeds per planting hole which produce an average of 8.61 tons / ha.